Go Global (Assessment and Module Kit to Boost up Intercultural Communication for Individuals Working Abroad) - Sarwari, Abdul Qahar; Muhammad Nubli, Abdul Wahab (2016)

(untitled)
This invention focuses on assessing the relationship among interpersonal communication competence (IPC), intercultural communication competence (ICC), and heart rate variability (HRV) of individuals who want to work abroad and dealing with people from different backgrounds.